Modulação do influxo de cálcio pelo peptídeo YY (3-36) em células do hipocampo de ratos - Domingues, Michelle Flores (2015)
Peptide YY (PYY) belongs to the neuropeptide Y (NPY) family, which also includes the neuropeptide Y (NPY) and pancreatic polipeptide (PP). These substances are biologically active, constituted of 36 aminoacids, and act via G protein coupled receptors. There are four functional subtypes of NPY family receptors in humans, namely Y1, Y2, Y4, and Y5. PYY is secreted by the intestinal L cells, being present in the blood stream in two active forms capable of crossing the blood brain barrier, PYY (1-36) and its cleavage product, PYY (3-36). PYY is a selective agonist for the Y2 receptor (Y2R) and has been identified as a modulator of appetite, promoting satiety sensation in mammals. Y2R are abundant in the brain hippocampus, where these receptors inhibit excitatory synaptic transmission and glutamatergic release when activated by potassium in hippocampal slices. Besides, knockout mice for Y2R present deficits in spatial and non-spatial memory tasks, showing a role of Y2R in learning and memory. The aim of this Master’s dissertation was searching for a better understanding of the interaction of PYY (3-36) and its Y2 receptor in CNS cells. For this purpose the activity of this peptide was investigated on Ca2+ influx in hippocampal cell cultures of Wistar neonate rats. We evaluated the influence of the presence of Ca2+ in the extracellular fluid, as well as the involvement of plasma membrane voltage-dependent Ca2+ and Na+ channels, and the influence of intracellular mechanisms related to the endoplasmic reticulum (ER), such as the SERCA pump, the inositol triphosphate (IP3) receptors and the ryanodine receptors (RyRs) in the responses induced by PYY (3-36) on the modulation of the [Ca2+]i, by using blockers specific for these channels. It was observed that the increase of the cytosolic [Ca2+] evoked by PYY (3-36) in hippocampal cells is independent of Ca2+ from the extracellular environment. Using a voltage-dependent Na+ channels blocker it was possible demonstrate that PYY (3-36) action is independent on Na+, suggesting that its activity on hippocampal cells does not induce or does not depend on cellular depolarization. In the experiments using RyRs or SERCA pump blockers it was observed an elevation of Ca2+ influx, that probably occurred due to the activation of SOCC, but with the concomitant presence of the a voltage-dependent Na+ channels blocker, this effect was abolished, suggesting a probable inhibition of SOCC channels in these conditions. In the experiments in the presence of an IP3Rs inhibitor, there was a decrease in cytosolic [Ca2+] evoked by PYY (3-36). The results from our experiments indicate that the action of PYY (3-36) on Ca2+ mobilization is mediated by intracellular receptors of the ER, suggesting that the observed elevation of [Ca2+]i is modulated especially by the activation of the intracellular Ca2+ signalling cascade through IP3 receptors.